Cdk4 and Cdk6 couple the cell-cycle machinery to cell growth via mTORC1 - Romero-Pozuelo, Jesús; Figlia, Gianluca; Kaya, Oguzhan; Martín-Villalba, Ana; Teleman, Aurelio A. (Cell reports, 2020)
Cell growth is coupled to cell-cycle progression in mitotically proliferating mammalian cells, but the underlying molecular mechanisms are not well understood. CyclinD-Cdk4/6 is known to phosphorylate RB to promote S-phase entry, but recent work suggests they have additional functions. We show here that CyclinD-Cdk4/6 activates mTORC1 by binding and phosphorylating TSC2 on Ser1217 and Ser1452. Pharmacological inhibition of Cdk4/6 leads to a rapid, TSC2-dependent reduction of mTORC1 activity in multiple human and mouse cell lines, including breast cancer cells. By simultaneously driving mTORC1 and E2F, CyclinD-Cdk4/6 couples cell growth to cell-cycle progression. Consistent with this, we see that mTORC1 activity is cell cycle dependent in proliferating neural stem cells of the adult rodent brain. We find that Cdk4/6 inhibition reduces cell proliferation partly via TSC2 and mTORC1. This is of clinical relevance, because Cdk4/6 inhibitors are used for breast cancer therapy.